THE RELATIONSHIP BETWEEN THE USE OF GAMES AND STUDENT LEARNING MOTIVATION AT SMAN 2 SIDOARJO - Wijayawati, Anik; Khamidi, Amrozi; Roesminingsih, Erny (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
High school students today are in a time when someone is experiencing changes within themselves. During the transition to adulthood, students are influenced by external factors that can lead them to be swayed by their environment, such as playing games. Students who have a high intensity of playing games may trigger a decrease in their learning moti-vation. The decrease in learning motivation among high school students is caused by several factors, including issues at school and relationships with parents and peers. The purpose of this research is to determine the relationship between game usage and learning motivation among stu-dents at SMA Negeri 2 Sidoarjo. This research is a non-experimental quantitative study, with a correlational research design using a cross-sectional approach. The respondents of the study consisted of 130 stu-dents from SMA Negeri 2 Sidoarjo, selected using purposive sampling technique. The data collection method used was a questionnaire. The analysis method used was Kendall's tau. The research results indicate that there is a relationship between game usage and learning motivation among students at SMA Negeri 2 Sidoarjo. The analysis results using the Kendall's tau test showed a p-value = 0.000, which means p-value < 0.05. The correlation coefficient value or r-value = -743 indicates a strong negative correlation, meaning that the higher the game usage, the lower the learning motivation among students. It can be concluded that there is a relationship between game usage and learning motivation among students at SMA Negeri 2 Sidoarjo